Can zero-valent iron nanoparticles remove waterborne estrogens?. (1st March 2015) - Jarošová, Barbora; Filip, Jan; Hilscherová, Klára; Tuček, Jiří; Šimek, Zdeněk; Giesy, John P.; Zbořil, Radek; Bláha, Luděk
Abstract: Steroidal estrogens are one of the most challenging classes of hazardous contaminants as they can cause adverse effects to biota in extremely low concentrations. They emerge in both waste waters and surface waters serving as a source of drinking water. Environmental Quality Standards for 17β-estradiol (E2) and 17α-ethinylestradiol (EE2), promulgated within the EU Water Framework Directive, are 0.4 and 0.035 ng L −1, respectively. Because nanoscale zero-valent iron (nZVI) particles have been previously used in numerous remediation technologies and have the advantage of possible magnetic separation, interaction of nZVI with E2 and EE2 in water was investigated to assess the potential role of nZVI in removing steroidal estrogens. A mixture of E2 and EE2 dissolved in water was shaken with varying doses of nZVI for 1–5 h. Concentration-dependent removal of the estrogens was observed but removal did not increase significantly with time. Concentrations of the estrogens were determined by HPLC/MS/MS and a biodetection reporter gene assay. Sorption and nonspecific oxygen-mediated oxidation of estrogens were identified as the most probable removal mechanisms. Two independent experiments confirmed that significant decrease of estrogens concentration is achieved when at least 2 g L −1 of nZVI is applied. The presented study provides insights into the mechanisms of nZVI interaction with steroidal estrogens under aerobic conditions prevailing in currently applied water treatment technologies. Graphical abstract: Highlights: Removal of waterborne estrogens by nZVI particles is evaluated. Estrogens are significantly removed by nZVI particles at doses 2 g L −1 or greater. Sorption and oxygen-mediated oxidation were identified as mechanisms of reaction.